2007
DOI: 10.1002/jbm.b.30923
|View full text |Cite
|
Sign up to set email alerts
|

Surface damage analysis of retrieved highly crosslinked polyethylene tibial components after short‐term implantation

Abstract: The use of highly crosslinked polyethylene (PE) in the knee remains controversial, because of reduced fatigue fracture properties of the material. The current study investigated postmelt surface damage as well as potential contributors to this damage in retrieved highly crosslinked PE tibial components, after short-term in vivo durations. Retrieved conventional PE tibial components were examined for comparison, as well as unused time zero highly crosslinked and conventional PE tibial components for inherent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
2
12
1
Order By: Relevance
“…However, the damage mechanisms observed in this cohort of retrievals exhibited mainly adhesive/abrasive wear mechanisms, as opposed to fatigue wear mechanisms. This is similar to a short-term (average implantation time=1.1 years) study that found the major damage mechanisms of remelted highly crosslinked polyethylene tibial inserts were abrasion, machine mark loss, and scratching [8]. This study also did not report delamination of the 13 HXLPE inserts that were analysed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the damage mechanisms observed in this cohort of retrievals exhibited mainly adhesive/abrasive wear mechanisms, as opposed to fatigue wear mechanisms. This is similar to a short-term (average implantation time=1.1 years) study that found the major damage mechanisms of remelted highly crosslinked polyethylene tibial inserts were abrasion, machine mark loss, and scratching [8]. This study also did not report delamination of the 13 HXLPE inserts that were analysed.…”
Section: Discussionsupporting
confidence: 85%
“…This study also did not report delamination of the 13 HXLPE inserts that were analysed. Interestingly, Willie et al did not observe any pitting in their retrieved specimens, although this may be attributed to the short implantation times [8]. Within both material groups in our collection, pitting, scratching, and burnishing were the predominant damage mechanisms.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Several factors associated with degradation of polyethylene material properties [53][54][55][56] and fatigue-related damage modes (e.g., delamination) [57][58][59][60][61][62] existed in these inserts. All simulated and retrieved inserts were sterilized using gamma radiation, were produced using polyethylene starting resin containing calcium sterate, and had nonconforming articular surfaces with relatively small tibiofemoral contact areas.…”
mentioning
confidence: 99%
“…The low conformity between the metallic femoral and the UHMWPE tibial insert shows large variations that significantly affect the contact stresses in the joint. Fatigue cracks can grow in the subsurface of UHMWPE and then propagate under cycling load leading to local fracture, pitting, and delamination, as it has been identified in retrieved implants (Liza et al, 2011;Willie et al, 2008). Most research into fatigue in polyethylenes is focused on the second step or crack propagation fatigue behavior, whereas few studies related to the total fatigue life involving the damage initiation step are to be found in the literature (Sobieraj, 2009;Oral et al, 2008;Baker et al, 2003).…”
Section: Introductionmentioning
confidence: 95%